Early Old English Nominal System: Synchronic Declensions in the Vespasian Psalter - Kolasińska, Paulina (Studia Anglica Posnaniensia, 2013)
The study analyzes the Early Old English nominal system from a synchronic perspective, since a diachronic approach is unable to provide an accurate description of the language. The analysis is based on the full text of the Vespasian Psalter interlinear gloss. The nouns were grouped according to their inflectional endings, thus representing the synchronically functioning nominal system of Early Old English, contrary to the traditional, diachronic classification, which uses reconstructed stems to classify nouns. The Vespasian Psalter model is compared and contrasted with the latest ‘classical’ work on Old English, Hogg and Fulk’s A Grammar of Old English. Volume 2: Morphology (2011), which also aims at presenting Old English from a synchronic perspective.